2005
DOI: 10.1111/j.1523-1755.2005.67139.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving NKF-K/DOQI™ bone metabolism and disease treatment goals with cinacalcet HCl

Abstract: In subjects on dialysis with secondary HPT, cinacalcet facilitates achievement of the K/DOQI-recommended targets for PTH, calcium, phosphorus, and Ca x P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
217
6
28

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 305 publications
(265 citation statements)
references
References 30 publications
14
217
6
28
Order By: Relevance
“…Both groups exhibited similar reductions in actual and percent changes in 6-mo intervals for PTH, CaϫP, Ca, and P levels following cinacalcet treatment. The efficacy data of the current study is consistent with analysis of pooled data from the four double-blind, placebocontrolled lead-in studies of cinacalcet in patients with SHPT and stage 5 CKD on dialysis and traditional therapies (vitamin D sterols and oral phosphate binder), showing cinacalcet to be significantly more effective than placebo at maintaining recommended levels of PTH, CaϫP, Ca, and P (19). Treatment-related AEs reported in the double-blind placebo-controlled studies among subjects randomized to cinacalcet were limited to nausea and vomiting, which were generally mild to moderate in severity and transient in duration.…”
Section: Discussionsupporting
confidence: 68%
“…Both groups exhibited similar reductions in actual and percent changes in 6-mo intervals for PTH, CaϫP, Ca, and P levels following cinacalcet treatment. The efficacy data of the current study is consistent with analysis of pooled data from the four double-blind, placebocontrolled lead-in studies of cinacalcet in patients with SHPT and stage 5 CKD on dialysis and traditional therapies (vitamin D sterols and oral phosphate binder), showing cinacalcet to be significantly more effective than placebo at maintaining recommended levels of PTH, CaϫP, Ca, and P (19). Treatment-related AEs reported in the double-blind placebo-controlled studies among subjects randomized to cinacalcet were limited to nausea and vomiting, which were generally mild to moderate in severity and transient in duration.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, it supports studies that have shown that cinacalcet has no clinically relevant interaction with standard immunosuppressive drugs (53). The most frequently reported treatmentemergent AE in the cinacalcet group was diarrhea, similar to what has been reported in other CKD cohorts (7,9,21,54). Previously, concerns have been raised about decreases in renal function following cinacalcet therapy for the treatment of persistent HPT including limited, but significant drops in eGFR (29).…”
Section: Evenepoel Et Alsupporting
confidence: 71%
“…These morphological transformations are associated with down-regulation of the vitamin D receptor and calcium-sensing receptor (CaSR), which result in parathyroid gland resistance to inhibitory feedback mechanisms (6). Successful renal transplantation corrects the physiologic and metabolic abnormalities responsible for the pathogenesis of secondary HPT (7)(8)(9). However, while endorgan resistance to the action of PTH rapidly wanes parallel to the recovery of renal function, regression of parathyroid gland hyperplasia is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Initial randomized controlled studies (RCT) with placebo arm recognized that cinacalcet could cause severe hypocalcaemia (<7.5 mg/dl) in up to 5 % of patients requiring oral calcium and/or vitamin D substitution [17]. Even more patients (35-45 %) experience digestive intolerance, in 8-15 %, requiring to terminate treatment [19,20,23] (EL 2b; RG B). The benefit of cinacalcet to improve bone mineral density is described; however, data are scarce and further studies with long-term follow-up are needed to substantiate this effect [24] (EL 3a).…”
Section: Resultsmentioning
confidence: 99%